2008
DOI: 10.1007/s00421-008-0877-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical response of finger flexor muscles during voluntary isometric contractions in elite rock-climbers

Abstract: To determine the differences between rock-climbers and controls in finger flexor (FF) motor units (MUs) features and activation strategy, eleven climbers and ten controls volunteered for the study. After maximal voluntary contraction (MVC) assessment, five levels of isometric contractions at 20, 40, 60, 80 and 100% MVC were performed. During contractions, electromyogram (EMG) and mechanomyogram (MMG) were recorded, from which the root mean square (RMS) and mean frequency (MF) were calculated. Climbers showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…Recently, MMG signal was also acquired during incremental aerobic exercise, with the aim to correlate MMG variables with some cardiopulmonary and metabolic parameters related to the anaerobic threshold [70,75]. Whereas correlations between MMG signal amplitude and frequency content and the level of force output were reported under both isometric [24,[49][50][51][52][53]64] and dynamic contractions [48,69,74,76], the use of MMG signal to evaluate muscle activation during aerobic tasks has been less investigated [70,75].…”
Section: Reliability Of Mmg Signalmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, MMG signal was also acquired during incremental aerobic exercise, with the aim to correlate MMG variables with some cardiopulmonary and metabolic parameters related to the anaerobic threshold [70,75]. Whereas correlations between MMG signal amplitude and frequency content and the level of force output were reported under both isometric [24,[49][50][51][52][53]64] and dynamic contractions [48,69,74,76], the use of MMG signal to evaluate muscle activation during aerobic tasks has been less investigated [70,75].…”
Section: Reliability Of Mmg Signalmentioning
confidence: 98%
“…On the other hand, the relationship between MMG signal frequency content and force output is mostly linear [53]. With these characteristics, MMG permitted to study the adaptations of neuromuscular activation strategies induced by several conditions, such as climbing [49] or resistance and aerobic training [55]. Also different physiological models, such as potentiation [56], muscle pain [57], hypoxia [58], hypothermia [59], muscle relaxation [60,61], while overimposing an electrical twitch stimulation during maximum voluntary contraction [62], or during spinal anaesthesia [63] could be also investigated.…”
Section: Mmg During Isometric Contraction ''In Vivo''mentioning
confidence: 98%
See 1 more Smart Citation
“…In the climbing grades paper written by Draper and co-workers (2011b), the authors highlighted inconsistencies in language and ability grouping criteria used to describe climbers and the problems this causes when attempting to make comparisons between studies (Grant et al, 1996;Grant el al., 2001;Boschker et al, 2002;Limonta et al, 2008;Esposito et al, 2009). Draper et al (2011b) proposed the nomenclature for climbing ability as shown in Table 1, establishing five groups from low grade to higher elite level climbers.…”
Section: Ability Groupingmentioning
confidence: 99%
“…Surface electromyography is widely used in the analysis of skeletal and also respiratory muscles whereas mechanomyographic signals are less common but they provide additional information on muscle activity to that obtained though electromyography (Esposito et al, 2009; Torres et al, 2010). Among the main advantages of these techniques it is noticeable that these measures are not invasive and allow a high temporal resolution that is very necessary to obtain information about the coupling between muscles within a respiratory cycle and between respiratory cycles.…”
Section: Introductionmentioning
confidence: 99%